On the gamma spectrum of multiplication gamma acts - Mehdi S. Abbas; Jubair, Samer A. (Kuwait Journal of Science, 2021)
In this paper we introduce the concept of topological gamma act as a generalization of Zariski topology . Some topological properties of this topology are studied. Under the concept of multiplication gamma acts various algebraic properties of topological gamma acts are given. We clarify the interplay between the properties of this topological space and the algebraic properties of the gamma acts under consideration . Also, the relation among this topological space and (multiplication ,cyclic ) gamma act was discussed . We also study separation axioms and compactness property in this topological space .